Kroncong Orchestration of Millennial Generation (Harmonia: Journal of Arts Research and Education, 2019)
Kroncong is the urban popular music of Indonesia, which some scholars suggest was brought by Portuguese in the early sixteenth century.Â  Kroncong becomes popular across the archipelago as accompaniment in its musical genre, theatre and film. Although popular music has long been an integral part of Indonesian cultural domain, genres such as kroncong have been overlooked by music scholars.Â  This article aims to introduce kroncong orchestration that could be performed in an updated style for incorporating repertoire from any other genres into idiomatic kroncong, that will be adopted by the millennial generation. Therefore, the reinvention of kroncong will not only be a significant contribution to scholarship on Indonesian popular music, but it will also contribute to a wider understanding of the complexities of indigenous ethnicity, political power, social class, and gender. The orchestration that will retain its rhythm pattern and vocal ornamentation, while reinforcing the strings and winds as melodic carriers.